Identifikasi Dini Kerusakan Jalan Flexible Pavement Dengan Menggunakan Algoritma PCA - Adhi Kusnadi; Ranny Ranny (Ultimatics : Jurnal Teknik Informatika, 2016)
Identifikasi of road damage and how to handle early is important so that the use of the road remains optimally. The delay in the repair process will exacerbate the damage to the road itself, and will certainly increase the cost of repairs. PCA algorithm was chosen because it is a technique that is commonly used to draw the features of the data on a high-dimensional scale. While the input of the system that is built in the form of a digital image of the damaged roads, has a relatively large dimensions to be used directly by the algorithm of pattern recognition, such as neural networks. Research results obtained this type of cracking cracked 67% and cracking the other 33%. This can be caused by a few things, namely the shooting process is not perfect, as the distance is too far, the less light, the edge detection process less well due to the method used is not appropriate. Index Terms—road damage, PCA, cracking, image, egde detection